Polysaccharides of Brassica rapa L. attenuate tumor growth via shifting macrophages to M1‐like phenotype. (29th June 2022) - Guo, Weiwei; Liu, Xiujun; Guo, Junting; Gao, Ruijuan; Xiang, Xiaodong; An, Xiqiang; Bai, Liping
Abstract: Macrophages are the major tumor‐infiltrating leukocytes, and tumor‐associated macrophages (TAM) play a critical role in cancer‐related inflammation since they show alternative polarization to M1 (tumor‐inhibited macrophages) or M2 (tumor‐promoted macrophages) phenotype. Brassica rapa L. ( B. rapa ) has been clinically proven to have anti‐tumor and immunity‐enhancing activity, and the polysaccharides of B. rapa (BRP) have been reported to have an immunoregulatory effect on macrophages. In this study, we focus on macrophage polarization to investigate the mechanism of anti‐tumor response of BRP in vivo and in vitro. We found that BRP improved the expression of M1 markers, including iNOS, COX‐2, HLA‐DR, CD11b and M1‐related cytokines. The expression of M2 markers Arg‐1, CD206 and CD163 induced by IL‐4 were inhibited by BRP treatment, resulting in the inhibition of tumor growth both in vivo and in co‐culture experiments in vitro. The activation of STAT signaling pathway were significantly regulated by BRP, which are important signals in TAM polarization. Overall, the results indicated that BRP has anti‐tumor effect through mediating macrophage polarization.